WHY NUTRITION EDUCATION? - Ganguli, B.; Mazumdar, Shukla (SCHOOL SCIENCE, 2012)
Hunger is the most important driving force … It demands food … Food is fuel of body machine … Search of ancient men – Hippocrates …17th century—Helmont, Sanctorius … Beginning of experimentation 18th Century—avoisier … 19th Century—period of exploration — Magendie, Liebig, Boussingult, Bidder, Schmidt, Voit, Rubner, Atwater, Lusk … Beginning of 20th century-Generalisation begins-Langworths law … Search for food dependent diseases … Discovery of Vitamins in 1912 … Advancement of food technology upto 1940 … Period of war and famine upto 1960 … Balance sheet of progress re-examined – result showed that a Frankenstein has been created so far as food is concerned … Human proclamation in 1963 from Rome – Hunger is still our enemy but malnutrition is worse … Strategy of this fight for nutrition at three areas – Analysis of food and nutritional problems, improvement of food production and distribution, and implementation of Nutrition Education.